Far-Red Light-Induced Azolla filiculoides Symbiosis Sexual Reproduction: Responsive Transcripts of Symbiont Nostoc azollae Encode Transporters Whilst Those of the Fern Relate to the Angiosperm Floral Transition - Dijkhuizen, Laura W.; Tabatabaei, Badraldin Ebrahim Sayed; Brouwer, Paul; Rijken, Niels; Buijs, Valerie A.; Güngör, Erbil; Schluepmann, Henriette (Frontiers in Plant Science, 2021)
Azolla ferns and the filamentous cyanobacteria Nostoc azollae constitute a model symbiosis that 22 enabled colonization of the water surface with traits highly desirable for development of more 23 sustainable crops: their floating mats capture CO2 and fixate N2 at high rates using light energy. Their 24 mode of sexual reproduction is heterosporous. Regulation of the transition from vegetative to spore-25 forming phases in ferns is largely unknown, yet a pre-requisite for Azolla domestication, and of 26 particular interest since ferns represent the sister lineage of seed plants. 27 A. filiculoides fern sporocarp formation required far-red light (FR), was increased by fern density, and 28 inhibited by nitrogen in the medium. Sporocarps induced with FR could be crossed to verify species 29 attribution of strains from the Netherlands but not from the Iranian Anzali lagoon; the latter strain was 30 assigned to a novel species cluster from South America. Red-dominated light suppresses the formation 31 of dissemination stages in both gametophyte and sporophyte-dominated lineages of plants, the response 32 likely is a convergent ecological strategy to open fields. 33 FR-responsive transcripts included MIKCC homologues of CMADS1 and miR319-controlled 34 GAMYB transcription factors in the fern, transporters in N. azollae, and ycf2 in chloroplasts. Loci of 35 conserved miRNA in the fern lineage included miR172, yet FR only induced miR529 and miR535, 36 and reduced miR319 and miR159. Phylogenomic analyses of MIKCC transcription factors suggested 37 that control of flowering and flower organ specification may have originated from the diploid to 38 haploid phase transition in the homosporous common ancestor of ferns and seed plants.